THE EFFECT OF MUAY THAI EXERCISE ON BALANCE AND FLEXIBILITY IN THAI ELDERLY - Sukmee, Kewarin; Khongprasert, Surasa; Laohapakdee, Ruht (Journal of Sports Science and Health, 2020)
Purpose : This study aimed to examine the effect of Muay Thai exercise on balance and flexibility in Thai elderly. Methods : Forty Thai males and females elderly, aged between 60-69 years, from the elderly club of Rangsit City Municipality in Pathum Thani Province participated in this study. Participants were screened by Physical Activity Readiness Questionnaire (PAR-Q) and randomly divided into 2 groups; a control group (n=20) and an experimental group (n=20). The experimental group practiced a session of 40 min of Muay Thai exercise, 3 days a week, for 8 weeks, whereas the control group receive no intervention. Balance and Flexibility were measured before and after the experiment. Data were analyzed in terms of means, standard deviation with paired t-test and independent t-test were used to compare differences within and between groups. The statistical significance was accepted at p<.05. Results : After 8 weeks of Muay Thai exercise, the mean of balance and flexibility were significantly increased significantly in the experimental group (p<.0.5). Moreover, the experimental group showed better improvements in balance and flexibility, compared to the control group. Conclusion : A 8-week Muay Thai exercise was effective for improving balance and flexibility in the elderly.